Register of Online Transactions in the Field of Beauty on Social Media Instagram - Rinda Roshita Dewi; Fitqi Sintiadi; Eva Utami Durahman (Universitas Teknokrat Indonesia, 2021)
This current research aimed to find out and describe the form of registers that are in the online buying and selling in the beauty field and to find out how the registers are formed. The online beauty shop was chosen because it considers a lot of enthusiasts and interactions between sellers and buyers in the buying and selling process. With the development of online beauty shops, it is possible has variations in the register used. Based on that reason, the author are interested in analyzing more about the register term found in the online beauty shop. The method used in this research is descriptive qualitative and data collection techniques used in this research are documentation. The data of this research are the register terms in two beauty online shops on Instagram. The source of data is written utterances from sellers and buyers that communicate during the online buying and selling process. The result of this research indicates that there are thirty five out of forty register terms which include in word formation process among others are ten register terms as abbreviations, one register terms as back formation, five register terms as clipping, six register terms as compounding, one register terms as inflection, four register terms as derivation, and the last is seven register terms as Indonesian affixation + English morpheme. The usage of register terms is influenced by the age, educational levels, and occupation of buyers.Keywords: register, online shop, sociolinguistics.